Coup d’œil sur la recherche : Implantation d’un programme de formation à l’offre active de services en français auprès des futurs professionnels de la santé et des services sociaux dans une université canadienne. - Consortium national de formation en santé; van Kemenade, Solange (2022)

Nursing students’ well-being: A comparison of two canadian nursing programs in different linguistic contexts - de Moissac, Danielle; Gueye, Ndeye Rokhaya; Vigier, Darcelle; Waddell, Candice; Graham, Jan Marie (Linguistic Minorities and Society, 2022)
Nursing programs are highly competitive and stressful environments; nursing educators are looking for ways to mitigate the negative consequences of demanding training programs. This article explores and compares the mental health status and sociodemographic and personal characteristics that influence the psychological distress of nursing and non-nursing students learning in either official language of Canada. An online and paper survey was administered during class time to 990 students, 186 of whom were in an undergraduate nursing program in one of two postsecondary institutions in Manitoba, Canada. Findings demonstrate that students in nursing programs are more likely to report poor mental health than students in other undergraduate programs and that nursing students in the French-language institution report poorer mental health outcomes as compared to nursing students in the English-language institution. Life satisfaction and high self-esteem are positively associated with well-being, whereas age, gender, and learning in a second language are risk factors contributing to anxiety. Keywords: mental health, risk behaviour, nursing students, linguistic minority, risk factors

Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières - Larocque, Sylvie; Lavoie, Anne. Marise; Muray, Kalum; Waja, Chamberline (Revue de la Diversité de la Recherche en Santé, 2021)
fs-ref-orig: Larocque, S., Lavoie, A. M., Muray, K. et Waja, C. (2021). Expérience des étudiants francophones issus d’immigrations récentes lors de leur première année d’étude en sciences infirmières. Revue de la Diversité de la Recherche en Santé, 4, 33-48. https://pubs.biblio.laurentian.ca/index.php/drhj-rdrs/Article de revue /view/324/287 fs-code-orig: Larocque-2021

La langue de travail des diplômés d’établissements postsecondaires de langue française, de langue anglaise ou bilingues - Lemyre, Étienne (2022)
pages: 22

Language used at work by graduates of English, French or bilingual postsecondary institutions - Lemyre, Étienne (Statistiques Canada, 2022)
pages: 20